Study of a magnetic alloy-loaded RF cavity for bunch compression at the CSR - 殷达钰 刘勇 夏佳文 李朋 赵永涛 杨磊 齐新 (Chinese physics C, 2010)
The Heavy Ion Research Facility and Cooling Storage Ring（HIRFL-CSR）accelerator in Lanzhou offers a unique possibility for the generation of high density and short pulse heavy ion beams by non-adiabatic bunch compression longitudinally,which is implemented by a fast jump of the RF-voltage amplitude.For this purpose,an RF cavity with high electric field gradient loaded with Magnetic Alloy cores has been developed.The results show that the resonant frequency range of the single-gap RF cavity is from 1.13 MHz to 1.42 MHz,and a maximum RF voltage of 40 kV with a total length of 100 cm can be obtained,which can be used to compress heavy ion beams of 238U72＋ with 250 MeV/u from the initial bunch length of 200 ns to 50 ns with the coaction of the two single-gap RF cavity mentioned above.